The prevalence of symptoms associated with pulmonary tuberculosis in randomly selected children from a high burden community. Issue 11 (21st October 2005) - Marais, B J; Obihara, C C; Gie, R P; Schaaf, H S; Hesseling, A C; Lombard, C; Enarson, D; Bateman, E; Beyers, N
Abstract : Background: Diagnosis of childhood tuberculosis is problematic and symptom based diagnostic approaches are often promoted in high burden settings. This study aimed (i) to document the prevalence of symptoms associated with tuberculosis among randomly selected children living in a high burden community, and (ii) to compare the prevalence of these symptoms in children without tuberculosis to those in children with newly diagnosed tuberculosis. Methods: A cross sectional, community based survey was performed on a 15% random sample of residential addresses. A symptom based questionnaire and tuberculin skin test (TST) were completed in all children. Chest radiographs were performed according to South African National Tuberculosis Control Program guidelines. Results: Results were available in 1415 children of whom 451 (31.9%) were TST positive. Tuberculosis was diagnosed in 18 (1.3%) children. Of the 1397 children without tuberculosis, 253 (26.4%) reported a cough during the preceding 3 months. Comparison of individual symptoms (cough, dyspnoea, chest pain, haemoptysis, anorexia, weight loss, fatigue, fever, night sweats) in children with and without tuberculosis revealed that only weight loss differed significantly (OR = 4.5, 95% CI 1.5 to 12.3), while the combination of cough and weight loss was most significant (OR = 5.4, 95% CI 1.7 to 16.9). Children with newly diagnosed tuberculosis reported no symptoms in 50% of cases. Conclusion: Children from this high burden community frequently reported symptoms associated with tuberculosis. These symptoms had limited value to differentiate children diagnosed with tuberculosis from those without tuberculosis. Improved case definitions and symptom characterisation are required when evaluating the diagnostic value of symptoms.